2019
DOI: 10.15405/ejsbs.248
|View full text |Cite
|
Sign up to set email alerts
|

Student Evaluation of International Interaction and Communication Opportunities at University

Abstract: This paper addresses the university campus environment for international interaction and communication by studying self-evaluation of local and international students. The research aims to determine which factors of the formal and informal learning environment as well as social interaction outside university influence students' quality perceptions of opportunities for international interaction and communication at university and how these factors affect student evaluations. The study developed and tested a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…For instance, Harder (2011) found that urban and suburban community colleges internationalized at higher rates than rural community colleges, a result that indicated additional research was needed in the latter category. Copeland et al (2017) developed the Community College Internationalization Index (CCID) to track internationalization efforts and account for institutional variation within the sector, but this tool has only been employed in one other context outside of the U.S. (see Kompanets and Väätänen, 2019). Though measuring internationalization efforts falls outside of the scope of this paper, future studies might build upon this work to explore how community colleges extend internationalization to their local communities as elaborated by internationalization plans or other institutional documents.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Harder (2011) found that urban and suburban community colleges internationalized at higher rates than rural community colleges, a result that indicated additional research was needed in the latter category. Copeland et al (2017) developed the Community College Internationalization Index (CCID) to track internationalization efforts and account for institutional variation within the sector, but this tool has only been employed in one other context outside of the U.S. (see Kompanets and Väätänen, 2019). Though measuring internationalization efforts falls outside of the scope of this paper, future studies might build upon this work to explore how community colleges extend internationalization to their local communities as elaborated by internationalization plans or other institutional documents.…”
Section: Introductionmentioning
confidence: 99%